GCK Gene Screening and Association of GCK Variants With Gestational Diabetes in North Indian Population. (October 2018) - Siddiqui, Samreen; Waghdhare, Swati; Gopi, Sundaramoorthy; Bhargava, Amit; Panda, Manju; Radha, Venkatesan; Mohan, Viswanathan; Dubey, Shweta; Jha, Sujeet
Background: GCK gene variants have been reported to be associated with gestational diabetes mellitus (GDM) in the Caucasian population. There are no reports exploring this association in the Indian population. Methods: This cross-sectional study included subjects from Max Super Speciality Hospital, New Delhi, India, over a span of 6 months. Females diagnosed with GDM as per the International Association of the Diabetes and Pregnancy Study Groups (IADPSG) criteria were enrolled. Direct gene sequencing was performed to screen all 10 exons and promoter region of GCK gene. Results: Out of the total 1000 females screened, 154 subjects had any degree of hyperglycemia. GCK gene screening was done and we observed 11 variants in 80.4% (41/51) of the GDM subset and 89.6% (43/48) of the controls. Allele frequencies of observed variants were not different between the control subjects (12.5%) and those diagnosed with GDM (8.4%). Conclusion: To the best of our knowledge, this is the first report from north India exploring association of GCK variants with GDM and we do not observe any association of GCK variants with GDM in our study population. CTRI Registration No : CTRI/2017/07/008964